Flow stress model for hydrogen degraded Inconel 718. (April 2018) - Ehrlin, Niklas; Fisk, Martin; Bjerkén, Christina
Abstract: For life time estimation, it is desirable to capture the lowering of yield strength and premature failure that some alloys exhibits when subjected to hydrogen. For this, a mechanism based material model has been developed to simulate the hydrogen enhanced localized plasticity (HELP) for the superalloy IN718. The model accounts for the increase in mobility of moving dislocations during plastic deformation, whenever hydrogen is present in the material. Tensile tests performed at four different strain rates: 5 × 10 −5, 5 × 10 −4, 5 × 10 −3 and 5 × 10 −2 s −1 show a difference in yield behaviour between hydrogen pre-charged and uncharged samples. No strain rate dependency of the hydrogen effect could be concluded. Two different hydrogen charging methods have been used: cathodic charging with molten salt as electrolyte, and high temperature gas charging. No differences in the tensile response could be seen between the two different charging methods. The proposed model was fitted against the experimental curves using a minimizing method and model parameters were obtained. Comprising iteratively updated parameters, the model is suited for implementation in finite element software.